Syzygium polyanthum extract-assisted biogenic synthesis of Co-doped Fe3O4 nanoparticles: structural, magnetic, and antimicrobial insights - Setyawan, Trio Erik; Nikmah, Ainun; Sesilia, Ni Kadek Nabila; Hidayat, Nurul; Sunaryono, Sunaryono; Diantoro, Markus; Susanto, Hendra; Nik Malek, Nik Ahmad Nizam; Fen, Yap Wing; Taufiq, Ahmad (John Wiley and Sons, 2026)
Co-doped Fe3O4 nanoparticles from iron sand with Syzygium polyanthum extract were successfully synthesized. The nanoparticle phase was exclusively Co-doped Fe3O4 with a cubic spinel crystal structure, where the replacement of Fe3+ (ionic radius = 69 pm) by Co2+ (ionic radius = 74 pm) enhanced the lattice parameters from 8.360 to 8.378 Å. The oxygen position parameter increased after cobalt substitution, with values ranging from 0.3890 to 0.3893. The overlapping Fe-O and Co-O bonds were detected in the range of approximately 442–534 cm–1 as a result of cobalt substitution. The success of S. polyanthum extract integration was confirmed by the presence of C-H (698–956 cm–1), C-O (1365 cm–1), and C-C (1636 cm–1) bonds, originating from phenolic compounds (flavonoids, saponins, and tannins) and aromatic compounds. The saturation magnetization decreased from 35.49 to 24.956 emu/g as the Co composition increased, which can be theoretically explained by Neel's sublattice model. Remarkably, the excellent broad-spectrum antimicrobial performance of the nanoparticles against different microbial strains (B. subtilis, E. coli, and C. albicans) can be attributed to the synergistic role of Co substitution and S. polyanthum extract. These findings demonstrate the utilization of natural resources to fabricate new broad-spectrum antimicrobial agents.